Tobacco Farming and its Socio-economic Determinants in Kushtia District of Bangladesh - Roy, Anupam; Naz, Sabrina; Mostafa, M. G. (Journal of Sustainability and Environmental Management, 2024)
Tobacco farming is profitable, earning a lot of money at once, and using unpaid family labor were the main reasons for tobacco farming. The study was carried out to explore the basic socio-economic determinants that significantly influence farmers in tobacco farming in Kushtia district of Bangladesh. The study was exploratory, combining primary and secondary data. Data were collected through a well-structured questionnaire in face-to-face interviews. The acreage of tobacco cultivation in Kushtia district for the last 10 years is decreasing at a rate of 4.65% per year. Labor shortages, high input cost, and health problems are the main reasons for the decline of tobacco cultivation. Tobacco cultivation requires a large amount of fertilizer (645 kg/acre). Profit per acre of tobacco, boro rice, wheat, and winter maize ware US 505.20, US 297.90, US 235.20, and US 353.80, respectively, with a Benefit-Cost Ratio (BCR) of maize (1.33)>tobacco (1.31)>wheat (1.28)>boro rice (1.25). The age of farmers and size of their own cultivated land had no effect on tobacco cultivation; larger farm and family size were more important, but educated people were less inclined towards tobacco cultivation. Governments can diversify tobacco growers or switch to more profitable crops such as maize as an alternative to tobacco to improve farmers' livelihoods.